Mass-Driven Orbital Eccentricity: The Dominant Role of Planetary Mass over Size in Shaping Explanatory Orbits - Goshu, Belay Sitotaw (Britain International for Academic Research (BIAR) Publisher, 2025)
The diversity of exoplanetary orbits, particularly their eccentricity, challenges traditional models of planetary dynamics, with planetary mass and size as potential drivers. This study investigates the dominant role of mass oversize in shaping orbital eccentricity, aiming to refine theoretical frameworks for exoplanetary systems. Observational data from 500 simulated exoplanets were analyzed to identify correlations between mass, size, and eccentricity with the Pearson correlation and statistical tests. Numerical simulations with REBOUND modeled mass-driven gravitational interactions, comparing eccentricity evolution across varying masses and radii. The model was fitted to propose a refined framework. Mass showed a weak positive correlation with eccentricity (r=0.15, p=0.002), while size had a negligible impact (r=0.08). Terrestrial planets exhibited higher mean eccentricity (0.299) than gas giants (0.234), suggesting external influences. Simulations confirmed mass-driven eccentricity growth (e.g., 0.004 at 10.0 M⊕), with size effects absent. The refined model, e ≈ 0.360⋅(M/M⊕)0.00001⋅(aratio)0.00001⋅(t/105), indicates a limited mass influence modulated by the system architecture. Mass primarily drives eccentricity, though system-specific factors amplify terrestrial eccentricities, impacting habitability. Future studies should use actual data, extend simulations, and include tidal effects to refine models, aiding habitability assessments in missions like TESS. This research advances our understanding of exoplanetary dynamics, emphasizing mass as a key determinant.